PERAN HUKUMAN DALAM MENINGKATKAN KEDISIPLINAN SHALAT BERJAMAAH SANTRI PUTRI PONDOK PESANTREN RAUDLATUSSALAM KECAMATAN GLENMORE - Nur Hafifah; Binti Setya Ningsih (Jurnal At-Taujih, 2022)
This research was motivated by the discipline of praying in congregation for female students of the Raudlatussalam Islamic Boarding School, Gunungsari, Glenmore District. Discipline of congregational prayer is determined by the role of punishment in improving the discipline of congregational prayer. This study aims to (1) determine the description of the discipline of congregational prayer for female students of the Raudlatussalam Islamic Boarding School, Gunungsari Glenmore. (2) knowing the form of punishment for female students of the Raudlatussalam Islamic Boarding School in Gunungsari Glenmorre who do not pray in congregation. This study uses a descriptive qualitative approach. Data collection techniques using the method of observation, interviews and documentation. The results of the study indicate that the discipline of praying in congregation for female students of the Raudlatussalam Gunungsari Islamic Boarding School is disciplined enough, seen from the sense of awareness, sense of responsibility, sense of obedience, and also feel deterred from the punishment they have received. As for the form of punishment in the form of physical punishment and fines, depending on the number of alpha prayers in congregation.